Sedimentary Facies of the Upper Part of Tapak Formation in Banyumas Area, Central Java - Ricky Andrian Tampubolon; Yan Rizal (Berita Sedimentologi, 2019)
The upper part of Tapak Formation in Kali Cimande of Banyumas area shows a good example of tidal flat succession. The interval consists of alternating sandstones, siltstone and mudstone that show a fining and thinning upward bedding pattern and includes sand flat, mixed flat and mud flat sedimentary facies. The sand flat facies is characterized by medium-grained sandstone, moderately sorted, with cross-lamination sedimentary structures and bioturbation trace fossils (Skolithos) found mostly on the top of sandstone layer. The mixed flat facies is characterized by an alternation of thin layered sandstones with mudstone and siltstone, with lenticular, wavy, and flaser sedimentary structures. This facies contains many forms of bioturbations, such as Planolites, Thallasinoides, Lockeia, and Ophiomorpha. The mud flat facies is characterized by repeated claystone and thin sandstone intercalation, where the ratio of clay content being more than 95 % of the total layers, and contains abundant Lockeia trace fossil. The Upper Tapak Formation in Banyumas basin has moderate reservoir potential.